Scapegoats : thirteen victims of military injustice - Scott, Michael, 1941- (Elliott & Thompson, 2013)
Thirteen fascinating diverse case studies offer a unique and human take on military history and the figure of the military scapegoatBeginning with defining the scapegoat and examining the conditions needed to qualify, this book then shares a history that is full of tales of those who have been wrongly castigated in the rush to find a culprit; only later, sometimes much later, when the real truth comes out, is the scapegoat exonerated. Exposed here, the real stories behind the myths that allow the reader to make a balanced judgment on history's fairness to the individual. From.